Changing surface wax compositions and related gene expression in three cultivars of Chinese pear fruits during cold storage - Dan Li; Yudou Cheng; Zhonglin Shang; Junfeng Guan (PeerJ, 2022)
The surface wax of fruit has a significant effect on abiotic stress and fruit quality. In this study, the composition of the waxes found on fruit surfaces and the related gene expression of three different pear cultivars (Xuehua, Yali, and Yuluxiang) were investigated during cold storage. The results showed that 35 wax compositions were found on the surfaces of the three pear cultivars, mainly including C29 alkane, three fatty acids, two esters, three aldehydes, three fatty alcohols, and three triterpenoids. The largest amount of C29 alkane, three fatty acids and two esters were found in Yuluxiang (YLX) on day 90, while aldehydes with carbons of C30 and C32 were the highest in Yali (YL). Xuehua (XH) showed the largest amount of C22 fatty alcohol on day 180 compared to YLX and YL. Larger amounts of triterpenoids were found in XH and YL when compared to YLX. The expression levels of fifteen wax related genes (LACS1, KCS2, KCS6, FDH, KCS20, GL8, CER10, CER60, LTPG1, LTP4, ABCG12, CER1L, CAC3, CAC3L, and DGAT1L) reached their peak at day 45 in YLX, compared to XH and YL, their expression levels in YLX were higher to different degrees. These results suggest that the different expression patterns of wax-related genes may be closely related to the difference in wax compositions of the surface wax of three pear cultivars.